TECHNOLOGY OF ORGANIZATION OF HEALTH-ENHANCING AND RECREATIONAL MOTOR ACTIVITY OF THE ELDERLY IN THE CONDITIONS OF FITNESS CLUB - Гакман; Hakman, Анна; Anna; Медвідь, Анжела; Abalasei, B.; Mindrescu, Veronica (Науковий часопис Національного педагогічного університету імені М.П. Драгоманова, 2021)
With regard to the ageing of Ukrainian population, events related to the involvement of the elderly in active aging and maintaining the health are becoming increasingly important. The purpose of the study is to theoretically and methodologically substantiate the technology of organization of health-enhancing and recreational motor activity of elderly people in the conditions of fitness club. The material and research methods. The achievement of the objectives rests upon the following research methods: theoretical analysis and generalization of data of scientific and methodical literature; pedagogical methods; sociological methods; methods of mathematical statistics. The research was conducted on the basis of the fitness club in Chernivtsi city. During this experiment, 132 elderly people aged 60-65 years were involved, including 84 women and 48 men. Results: Theoretical analysis of scientific works of foreign and domestic scientists has shown that fundamental and applied research on these topics are systematically conducted in many countries. However, the development and implementation of technology for the organization of health-enhancing and recreational physical activity for the elderly is insufficiently studied. We have determined that the purpose of the author's technology is to involve the elderly in regular health-enhancing and recreational motor activity in a fitness club, which is aimed at improving life position and quality of life, increasing overall performance. The components of technology are defined. They are: value-oriented, emotional-evaluative and cognitive-reflexive. Active and proactive levels of technology are analyzed. Conclusions. The obtained data reveal the possibilities and prospects of using health-enhancing and recreational motor activities for the elderly in a fitness club. The prospects for further researches are aimed at increasing the level of involvement of the elderly in health-enhancing and recreational physical activity and, as a consequence, improving the health of Ukrainians.
Keywords: old age, health-enhancing and recreational motor activity